A Job Training Report as an Asisstant Journalist of The International Division at Jawa Pos Group Surabaya from 7th January to 14th February 2014 - Muh. Jauhar Navis, SN.: 121101026 (2014)
Information is very important in the world, because it leads to an increase in understanding and decrease in uncertainty. Every mass media provides local and international news which contain a lot of information from their country and other countries. Newspaper is one of the sources of information that present actual news, informative, and updated news.